2020
DOI: 10.1111/aas.13542
|View full text |Cite
|
Sign up to set email alerts
|

Telephone triage performed by nurses reduces non‐urgent ambulance missions: A prospective observational pilot study in Finland

Abstract: The increasing number of calls made to emergency medical communication centres (EMCCs) and emergency medical services (EMS) represents a challenge among welfare states. 1-4 In Finland, EMCCs, organized by the national dispatch authority, handle about 2.7 million emergency calls and dispatch about 750000 EMS missions annually. The dispatch protocols for EMS are primarily designed to identify patients who require emergency care, but assessing nonurgent situations often fails. 4-6 In the Finnish integrated EMCC s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 17 publications
(56 reference statements)
0
12
0
2
Order By: Relevance
“…The effectiveness of phone assessment has been highlighted in previous research. One-third of people calling the triage nurse were satisfied with the care instructions or guidance from social and health care services [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of phone assessment has been highlighted in previous research. One-third of people calling the triage nurse were satisfied with the care instructions or guidance from social and health care services [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of a phone assessment has been highlighted in previous research. It showed that one-third of the callers to the triage nurse were satis ed when they got care instructions or guidance to social and healthcare services (47). Furthermore, this telecare offers new possibilities for patients, especially in rural areas, and for all healthcare workers to be able to help and advice citizens safely by phone, e.g., like during outbreaks of contagious diseases (48).…”
Section: Discussionmentioning
confidence: 99%
“…Die Etablierung einer gemeinsamen Telefonnummer für Rettungsdienst und ÄBD scheint ein Lösungsweg zu sein [ 1 , 10 , 16 , 18 , 21 , 27 ]. Dies wurde in einigen Regionen Deutschlands als Modellprojekt realisiert und ist in vielen Ländern Europas seit Jahren erfolgreich etabliert [ 10 , 14 , 17 , 22 ].…”
Section: Diskussionunclassified
“…Über eine solche Nummer kann nach einer standardisierten Abfrage eine Zuweisung zum geeigneten System erfolgen [ 1 , 10 ]. Somit könnte man auch Patienten, die die Dringlichkeit der Situation fehleinschätzen, schnell der richtigen Versorgungsform zukommen lassen [ 1 , 10 , 21 ]. Dies würde die Patienten von der Verantwortung entlasten, in einer für sie belastenden Situation diese schwierige Entscheidung treffen zu müssen [ 27 ].…”
Section: Diskussionunclassified